(untitled) (Development Service Industry Management, 2024)
The article emphasizes the priorities of organizations in the IT sector and singles out ensuring the efficiency of business processes as one of them. The importance of compliance by IT sector organizations with a resource approach to ensuring the efficiency of business processes is substantiated, in which, in addition to the basic components (financial, material and technical and other resource support), it is important to develop intellectual capital, strengthen innovativeness and investment attractiveness. Thus, it is proposed to consider the mechanism for ensuring the efficiency of business processes of IT sector organizations as a component of the management system, the vectors of which are aimed at establishing effective business activities in the conditions of digitalization of the economy. The conceptual provisions for the formation and implementation of the mechanism for ensuring the efficiency of business processes of IT sector organizations in the conditions of digitalization of the economy were formed, where the importance of improving the management system for ensuring the efficiency of business processes and increasing the efficiency of the use of economic levers for managing business processes was highlighted. The mechanism for ensuring the efficiency of business processes of organizations of the IT sector should be considered as one of the main factors of their development and competitiveness. The main focus of the mechanism for ensuring the efficiency of business processes of IT sector organizations is to optimize the use of resources. The resource management system for ensuring the efficiency of business processes in IT sector organizations can achieve the expected results only if it enables not only rational use of available resources, but also provides an active systematic search for opportunities for further development.